Fiscal Monitor, April 2018 : Capitalizing on Good Times. (Fiscal Monitor; Fiscal Monitor ;, 2018)
This report discusses fiscal trends in policies aimed at reducing fiscal vulnerabilities and boosting medium-term growth, recent fiscal developments and the fiscal outlook in advanced economies, emerging markets, and low-income developing countries; recent trends in government debt and analysis of changes in fiscal balances, revenue, and spending; potential fiscal risks; and growth from the fiscal policies. It also describes how digitalization can help governments improve implementation of current policy and widen the range of policy options, and opportunities and risks for fiscal policy, including improvements in policy implementation, the design of future policy, and how digitalization can create opportunities for fraud and increase government vulnerabilities.